ANALYSIS OF LEARNING RESOURCE NEEDS OF LEARNING MANAGEMENT SYSTEM ON GEOGRAPHY SUBJECTS - Fitri Bugis; Murti Kusuma Wirasti; Yuliani Nurani (International Forum of Researchers and Lecturers, 2022)
The purpose of the study is to determine the student's need for learning resources by using Learning Management System (LMS) in geography subjects. The research method is quantitative with a research sample of class XI SMA N 3 OKU students who took geography subjects which were carried out with random sampling. The instruments used in this study were questionnaires and interviews, while the analysis method used Descriptive analytics. The tendency shows that presentations of 95% like online learning. The results of the questionnaire sources from the indicators of the need to pay attention to the 68.5% tendency of students that strongly agree and 31.5% agree if an LMS learning media was developed using Video. Besides the video, media of PPT and pdf documents also appear as options. Based on the results of this research, it can be concluded that it is necessary to develop LMS-based learning resources by combining more videos, then followed by PPT and pdf. Moreover, the assembling process must apply the science of piracy design which is not just uploading material.